Physical properties of juvenile wood of two paulownia hybrids : Fizička svojstva juvenilnog drva dvaju hibrida paulovnije - Sedlar, Tomislav (Array, 2020)
There is a growing trend in the world of planting fast growing species (rotations 5 to 10 years). Their primary purpose is the production of wood fibers and biomass, but they certainly represent the potential in making solid wood products as well. One of the fast-growing species is Paulownia sp., a species of extremely fast growing wood. Plantation breeding of Paulownia sp. in Croatia is increasing, although there is a little knowledge about the technical properties of Paulownia wood and its end use is questionable. This paper presents preliminary results of some physical properties of juvenile wood of two Paulownia hybrids planted in the area near the town of Glina in the Republic of Croatia. One hybrid is 9501 ((Paulownia fortunei × Paulownia elongata) × (Paulownia fortunei × Paulownia tomentosa)) and the other hybrid is Shan Tong (Paulownia fortunei × Paulownia tomentosa). The aim of this study was to investigate physical properties of juvenile wood of two Paulownia hybrids from one site in Croatia, to determine differences in physical properties of wood between two hybrids and to evaluate the correlation between density and shrinkages of each hybrid. Significant differences in oven dry density, basic density and density at maximum MC, between the two hybrids were determined. There is no statistically significant difference in longitudinal, radial, tangential and volumetric shrinkages between the two hybrids.